PROPRIEDADES FÍSICAS E MECÂNICAS DE PAINÉIS LVL DE Eucalyptus grandis - Palma, Hernando Alfonso Lara [UNESP]; Ballarin, Adriano Wagner [UNESP] (Universidade Federal de Santa Maria, 2011)
This paper mainly aimed to evaluate the physical and mechanical properties of LVL panels made from Eucalyptus grandis, from reforestation at the region of Sengés, in Paraná state, Brazil. LVL panels were manufactured using 23 veneers (2,4mm thick each one) in commercial dimension of 2.500 mm long and 1,200 mm wide. The properties of static bending were analyzed (strength and rigidity) in beams of the LVL, in the flatwise and edgewise positions. The properties of compression parallel to grain and shear parallel in the plans L-X and L-Y and density in this LVL panels were also analyzed according to ASTM-D 5456/4761 and ASTM-D 198 codes. The mean values to flatwise bending MOE and MOR were 13114 MPa and 88.76 MPa, respectively, and for edgewise bending MOE and MOR were 15871 MPa and 88.63 MPa, respectively. The density (12%) of the LVL panels and of the veneers were 690 kg/m3 and 649 kg/m3. The mean values to parallel compression MOE and MOR were 16856 MPa and 58.05 MPa, respectively. The mean values of the maximum resistance to shear parallel in the plans L-X and L-Y were 5.96 MPa and 591 MPa, respectively. All these values reached partially or they passed the medium limits of reference (normative codes, researches and commercial catalogs) established for LVL panels and original solid wood, attesting overall the quality of those panels produced with this wood.

O presente trabalho teve como objetivo principal avaliar as propriedades físicas e mecânicas de painéis LVL (Laminated veneer lumber) confeccionados com lâminas de Eucalyptus grandis, provenientes de reflorestamentos da região de Sengés, Paraná - Brasil. Foram confeccionados painéis LVL de 23 lâminas, de dimensões comerciais de 2500 mm de comprimento, 1200 mm de largura e espessura nominal de 50 mm (lâminas de 2,4 mm). Em vigas retiradas dos painéis LVL foram analisadas as propriedades de flexão estática (rigidez e resistência), nas condições de menor inércia (flatwise) e de maior inércia (edgewise), compressão paralela, cisalhamento paralelo nos planos L-X e L-Y e densidade, atendendo às prescrições das normas ASTM-D 5456/4761 e ASTM-D 198/143. Os valores médios obtidos para o módulo de elasticidade e resistência à flexão estática foram, respectivamente, 13114 MPa e 88,76 MPa para o ensaio na condição de menor inércia e de, respectivamente, 15871 MPa e 88,63 MPa para o ensaio na condição de maior inércia. A densidade aparente (a 12% de umidade) dos painéis LVL e das lâminas foram, respectivamente, 690 kg/ m3 e 649 kg/m3. Os valores médios obtidos nos ensaios de compressão paralela foram 16856 MPa para o módulo de elasticidade e 58,05 MPa para a resistência. Os valores médios da resistência no ensaio de cisalhamento paralelo no plano L-Y e no plano L-X foram 5,96 MPa e 5,91 MPa, respectivamente. Todos esses valores atingiram parcialmente ou ultrapassaram os limites médios de referência estabelecidos para painéis LVL e para a madeira sólida originária, atestando, sobretudo, a qualidade dos painéis produzidos com essa madeira.
PHYSICAL AND MECHANICAL PROPERTIES OF LVL PANELS MADE FROM Eucalyptus grandis
Keywords: LVL panels; Eucalyptus grandis; static bending; compression parallel; painéis LVL; Eucalyptus grandis; flexão estática; compressão paralela